“Value of science for the user” - scientific research as an element of a comprehensive assessment of scientific units - the status de lege lata and the postulates de lege ferenda in the light of own research - Monika Porwisz; Jarosław Radosław Truchan; Bartłomiej Pączek; Iwona Klonowska; Ewa Kuczyńska (Journal of Modern Science, 2025)
Objectives The aim of the research was to learn about the opinions of project managers on their management of projects implemented at the Police Academy in Szczytno in the years 2017-2022. An important issue was to learn about the conditions of project management in the organization in which they operate, as well as factors influencing the efficiency and effectiveness of their management.